2020
DOI: 10.1007/s00592-020-01590-w
|View full text |Cite
|
Sign up to set email alerts
|

Real-world adherence, persistence, and in-class switching during use of dipeptidyl peptidase-4 inhibitors: a systematic review and meta-analysis involving 594,138 patients with type 2 diabetes

Abstract: Aims Medication adherence and persistence are important determinants of treatment success in type 2 diabetes mellitus (T2DM). This systematic review and meta-analysis evaluated the real-world adherence, persistence, and in-class switching among patients with T2DM prescribed dipeptidyl peptidase-4 (DPP4) inhibitors. Methods MEDLINE, EMBASE, Cochrane Library, PsychINFO, and CINAHL were searched for relevant observational studies published in the English language up to 20 December 2019. This was supplemented by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…In this regard, the present study offers data over 3 years and, a more reliable indication, especially in terms of persistence. Most studies stop at 12 months of analysis 32 …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the present study offers data over 3 years and, a more reliable indication, especially in terms of persistence. Most studies stop at 12 months of analysis 32 …”
Section: Discussionmentioning
confidence: 99%
“…The speculation that regimen complexity or the severity of diabetes may not necessarily lower adherence to DPP4 inhibitors [ 23 ] was supported by several studies [ 57 59 ]. Common reasons for discontinuing DPP4 inhibitors were inadequate glycemic control and intolerance, as with other antidiabetic medications [ 61 ].…”
Section: Dipeptidyl Peptidase-4 Inhibitorsmentioning
confidence: 99%
“…The discontinuation rate in RCTs was 31.8% (17.0%; 46.7%) in a total of 7 studies evaluated and the mean persistence rate was 56.2% (46.1%; 66.3%) in a total of 6 studies evaluated [50]. In another systematic review and meta-analysis that included 34 cohort studies involving almost 600,000 patients with T2D receiving oral an antidiabetic drug, 56.9% (49.3%; 64.4%) of patients with T2D were adherent at one year (proportion of days covered or medication possession ratio ≥0.80) and 44.2% (36.4%; 52.1%) at two years [51]. A third systematic review and meta-analysis comprising 48 studies showed that adherence was better for sulphonylureas (SUs) and thiazolidinediones when compared with metformin.…”
Section: Treatment Adherencementioning
confidence: 99%